A New Concept Proposal of the Tidal Level Designed for the Security of Coastal Levee during Storm Surge — Taking the Lingdingyang Estuary as an Example - LI Bin; HE Yong; FANG Shenguang (Renmin Zhujiang)
Based on the analysis of the design frequency tidal levels,storm surge water increase and flood inflow upstream of control stations in Lingdingyang Estuary over years,it showed that the tidal levels of designed frequency of 0.5%~2.0% raised from 0.2 to 1.0 m in recent years,the extreme storm surge elevations exceed 2.5 m commonly,and the current tidal level difference of adjacent design frequency was less than 0.2 m.During the emergence of the extreme storm surge elevation in the estuary flood upstream would not be appeared simutaneously,while the moderate tide was most likely encounterred.Therefore,there were some problems in the application of design frequency tidal levels in estuarine waters,such as the small tidal level difference between adjacent frequencies,the severe frequency jump of tide level during strong typhoon,and the failure to directly reflect the leading role of the extreme storm surge elevation in the elevation design of coastal levee.The concept of the tidal levels designed for storm surge security of coastal levee was proposed in the paper,which were composed of multi-year average high tidal level and the maximum extreme storm surge elevation,clearly and easily to be used.It highlights the main role played by coastal levee to resist the disaster by strong storm surge.The calculated values were close to and slightly more than the designed tidal levels of 100~200 year return period of main stations in the mouth of Lingdingyang estuary,Shiziyang water area and delta river network area after reviewed in 2020,proving its safety and reliability.The reviewed tidal levels of designed frequency in the Chiwan station in 2020 were likely too high by analysis preliminarily.The tidal level designed for storm surge security of coastal levee could be widely used in reinforcement design,safety risk assessment in storm surge and storm surge disaster warning and response.